Qualitative research approaches for public administration - Kokab, Adila (Society Publishing, 2018)
This book highlights the various approaches, tools and techniques that are used in a qualitative way in order to support the work of public administrators. The book is divided into ten chapters which are thematically arranged in order to encapsulate the principal aspects of this type of research paradigm. This book is meant to support those who take an interest in research for purposes of supporting the work of government and non-governmental agencies. It is also relevant to public administrators in as far as it gives them an insight into how and why the data which they use in their work is collected. The book highlights methodological challenges and opportunities that might be of interest to a researcher. It then raises heuristic dimensions by challenging the notion that qualitative research is inherently inferior to quantitative research.